Functional regeneration of ligament-bone interface using a triphasic silk-based graft. (November 2016) - Li, Hongguo; Fan, Jiabing; Sun, Liguo; Liu, Xincheng; Cheng, Pengzhen; Fan, Hongbin
Abstract: The biodegradable silk-based scaffold with unique mechanical property and biocompatibility represents a favorable ligamentous graft for tissue-engineering anterior cruciate ligament (ACL) reconstruction. However, the low efficiency of ligament-bone interface restoration barriers the isotropic silk graft to common ACL therapeutics. To enhance the regeneration of the silk-mediated interface, we developed a specialized stratification approach implementing a sequential modification on isotropic silk to constitute a triphasic silk-based graft in which three regions respectively referring to ligament, cartilage and bone layers of interface were divided, followed by respective biomaterial coating. Furthermore, three types of cells including bone marrow mesenchymal stem cells (BMSCs), chondrocytes and osteoblasts were respectively seeded on the ligament, cartilage and bone region of the triphasic silk graft, and the cell/scaffold complex was rolled up as a multilayered graft mimicking the stratified structure of native ligament-bone interface. In vitro, the trilineage cells loaded on the triphasic silk scaffold revealed a high proliferative capacity as well as enhanced differentiation ability into their corresponding cell lineage. 24 weeks postoperatively after the construct was implanted to repair the ACL defect in rabbit model, the silk-based ligamentous graft exhibited the enhancement of osseointegration detected by a robust pullout force and formation of three-layered structure along with conspicuously corresponding matrix deposition via micro-CT and histological analysis. These findings potentially broaden the application of silk-based ligamentous graft for ACL reconstruction and further large animal study.